PRONAF: ruptura do padrão de financiamento oficial da agricultura brasileira? - Santos Filho, João Mendes dos (2003)
The Brazilian State begins to have a more active participation in rural credit with proposals for intervention in the commercialization and financing of coffee with the creation, in 1937, of the Agricultural and Industrial Credit Portfolio of Banco do Brasil (CREAI). However, until the 1960s, according to Cabral (2001), the Financial System did not have a truly organized institutional framework for directing rural credit, as this type of credit was based on monetary issuance and Banco do Brasil, its main provider , was a monetary authority. Brazilian agricultural policy underwent a change in focus from the 1960s, seeking to modernize the country's agriculture. Government actions began to intervene more and more in the formatting of a model that would increase productivity with the aid of modern cultivation techniques. Thus, the internalization of the capital goods department (Dl) for agriculture started to receive government attention in the search for a new standard in the dynamics of Brazilian agriculture. With the creation of the National Rural Credit System (SNCR), in 1966, regular credit protection emerged that aimed to encourage the use of so-called "modern inputs" and increase production and productivity, making Brazilian products more competitive on the market international, in addition to providing the agricultural sector with better conditions in the financial market, such as easy access to credit, favorable interest rates and longer terms (OLIVEIRA & MONTEZANO, 1982). “The SNCR created payment conditions compatible with the specificities of the rural sector and enabled favorable interest rates with the objective of making rural profitability via a logic of agricultural industrialization creating the institutionality that supported agricultural credit until the 1980s” ( CABRAL, 2001). The resources necessary for its execution came from: a) funds linked to the rural sector; -b) values ​​related to exemptions from payments; c) own resources of members of the rural credit system; d) amounts paid to the Central Bank (BACEN) by the banking system (compulsory payment); e) rural credit bonds, mortgages or similar bonds issued by government members of the system; f) proceeds from fines; g) result of sector financing operations; and h) resources from external sources.